Fatty Acid Methyl Esters From the Coral-Associated Bacterium Pseudomonas aeruginosa Inhibit Virulence and Biofilm Phenotypes in Multidrug Resistant Staphylococcus aureus: An in vitro Approach - Vijay, Karuppiah; Kiran, George Seghal; Divya, S.; Thangavel, Kavitha; Thangavelu, Sathiamoorthi; Dhandapani, Ranjithkumar; Selvin, Joseph (Frontiers in Microbiology, 2021)
In an attempt to study the antibacterial, antivirulence and antibiofilm potentials associated with bacteria residing the tissue and surface mucus layers of the pristine corals, we screened a total of 43 distinct bacterial morphotypes from the coral Favites sp. and identified the bacterium Pseudomonas aeruginosa strain CBMGL12 with excellent antibacterial, antivirulence and mild antibiofilm potential against the multidrug resistant pathogenic strains of Staphylococcus aureus (reference strain: MTCC96; community-acquired methicillin resistant strain: CA-MRSA). Extracellular metabolites from the coral-associated bacterium Pseudomonas aeruginosa were solvent extracted, fractionated by chromatographic techniques such as silica column and HPLC-UV with concomitant bioassays guiding the fractionation of metabolites. Identification of bioactive chemical moieties was performed by FT-IR analysis, GC-MS/MS equipped with NIST library, 1H and 13C NMR spectral studies. We report the differential production of extracellular and cell-associated virulence and biofilm phenotypes in Multi-drug resistant strains of Staphylococcus aureus, post-treatment with the identified aromatic fatty acid methyl esters (FAME) such as methyl benzoate and methyl phenyl acetate produced by the coral-associated bacterium. In conclusion, the study has identified antibacterial, antibiofilm and antivirulent FAME from the coral-associated bacterium Pseudomonas aeruginosa for its ability to attenuate virulence and biofilms phenotypes in multi-drug resistant pathogenic strains of Staphylococcus aureus.